Analytical tools for quantifying the morphology of invertebrate trace fossils. (July 2014) - Lehane, James R.; Ekdale, A. A.
Abstract : The analysis of trace fossils usually is performed qualitatively, which makes comparing trace fossils from different units less objective than quantitative approaches. Quantifying the shape of trace fossils enables scientists to compare trace fossils described by different people with greater precision and accuracy. This paper describes several methods for quantifying invertebrate trace fossils, including morphology dependent methods (motility index, mesh size, topology, tortuosity, branching angle, and the number of cell sides) and morphology independent methods (fractal analysis, burrow area shape, and occupied space percentage (OSP)). These tools were performed on a select group of graphoglyptid trace fossils, highlighting the benefits and flaws of each analytical approach. Combined together, these methods allow for more objective comparisons between different trace fossils.